The economic risk analysis in the case of agricultural enterprises - Kulcsár, Edina (Acta Agraria Debreceniensis, 2013)
The company’s activity, profitability and growth potential are influenced by risk and uncertainty derived from the economic environment. The principal thing that makes difference between risk and uncertainty is the capacity to be quantified, and then the risk can be measured, whereas uncertainty is not. Specific risk types of agricultural enterprises are on the one hand the economic risk and specific risk arising from the main agricultural activity. The economic risks include financial risk categories like market risk, liquidity risk, credit risk and operational risk. Macroeconomic risk manifest also a significant influence to the company and the importance of taking into account of this, importantly increased in recently years. In present paper, I quantified the total risk of company by using financial and operating leverage indicators. The company’s growth was characterized with internal growth rate and sustainable growth rate. The present research aims to explore risk and growth level of agricultural companies and grouping companies by different characteristics. In present analysis I have used cluster analysis. From the results I can summarize, that the agricultural enterprises growth is made by using internal financing resources and their financial leverage level is lower that operating leverage level.